Organic maize grown with Herbaspirillum seropedicae and Azospirillum brasilense associated with green manures - Joseani S. Ávila; Joilson S. Ferreira; Rayka K. A. Santos; Pablo A. da Rocha; Maida C. D. de Lima (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Organic maize cultivation is gaining relevance in the agricultural sector due to its rising profitability for producers and its contribution to reducing environmental impacts. This study aimed to evaluate the effects of green manure and inoculation with diazotrophic bacteria on maize yield under an organic cropping system. The experiment was conducted at Sítio Vale da Jaqueira, an organic-certified area located in the village of Estiva, municipality of Vitória da Conquista, Bahia, Brazil. A randomized block design in a 4 × 3 factorial scheme was used, with factors consisting of green manure (velvet bean, sunn hemp, jack bean, and weeds) with and without inoculation using Herbaspirillum seropedicae and Azospirillum brasilense, with four replications. The association between H. seropedicae and jack bean resulted in a 44.91% increase in grain yield compared to the control, providing a viable alternative for organic maize cultivation.